Magnetic wedge and rotary electric machine
The magnetic wedge, featuring flat magnetic metal particles, interposed phases, and a surface coating layer, addresses the limitations of existing wedges by reducing harmonic losses and enhancing magnetic and thermomechanical properties, thereby improving the efficiency and reliability of rotating electric machines.
Patent Information
- Application Number
- JP2023156245
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2043-09-21
AI Technical Summary
Existing magnetic wedges in rotating electric machines suffer from high harmonic losses due to low magnetic permeability, magnetic saturation, and inadequate thermal and mechanical properties, limiting the efficiency improvement range of these machines.
A magnetic wedge comprising a plurality of flat magnetic metal particles with interposed phases and a surface coating layer, designed to enhance magnetic, electrical, and thermomechanical properties, thereby improving the efficiency and reliability of rotating electric machines.
The proposed magnetic wedge structure effectively reduces harmonic losses, enhances magnetic permeability, and improves thermal stability and mechanical strength, leading to increased efficiency and reliability of rotating electric machines.
Smart Images

Figure 2025047640000001_ABST
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to a magnetic wedge and a rotating electric machine. [Background technology]
[0002] Usually, the coil winding of a rotating electric machine is housed in an iron core slot and supported and fixed by a wedge provided at the slot opening. A non-magnetic material is generally used for the material of the wedge, but since the magnetic resistance value in the gap between the stator iron core and the rotor iron core becomes discontinuous, pulsation occurs in the magnetic flux distribution on the iron core surface facing the wedge through the gap, and harmonic loss increases. In order to reduce this harmonic loss, a wedge with moderate magnetic properties (magnetic wedge) has been provided for some time. By applying the magnetic wedge, harmonic loss is reduced and the efficiency of the rotating electric machine is improved. FIG. 1 is a schematic diagram of the use state of the magnetic wedge and the effect of the magnetic wedge. FIG. 1 shows a radial gap type rotating electric machine as an example. FIG. 1 shows a magnetic wedge 100, a coil 230, an iron core tooth 250, and an iron core slot 260.
[0003] It goes without saying that the higher the magnetic permeability of the magnetic wedge, the more the harmonic loss can be reduced. However, as shown in FIG. 1, the magnetic wedge is arranged so as to bridge the adjacent iron core teeth, and therefore there is a drawback in that the leakage magnetic flux flowing between the iron core teeth through the magnetic wedge increases. In addition, the existing magnetic wedge is prone to magnetic saturation due to its low saturation magnetization, and furthermore, has a large loss (high coercive force results in large hysteresis loss, and low electrical resistivity results in large eddy current loss), so the efficiency improvement range of the rotating electric machine is limited. In addition, the existing magnetic wedge has a low magnetic permeability, so the efficiency improvement range of the rotating electric machine is limited, and it is insufficient in terms of thermal stability and mechanical properties (strength, toughness). Therefore, it is desired to improve the properties of the magnetic wedge in terms of saturation magnetization, magnetic permeability, loss, strength, toughness, etc. In particular, it is desired to improve the magnetic properties, electrical properties, and thermomechanical properties of the magnetic wedge. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Utility Model Application Publication No. 58-6572 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a magnetic wedge and a rotating electric machine having excellent electrical properties and heat resistance (electrical properties, magnetic properties, and mechanical properties). [Means for solving the problem]
[0006] The magnetic wedge of the embodiment is a magnetic wedge for a rotating electric machine, and the magnetic wedge is a magnetic wedge that includes a plurality of flat magnetic metal particles, an intervening phase, and has a surface coating layer on at least a portion of the surface of the magnetic wedge. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic diagram showing the use of a magnetic wedge and the effect of the magnetic wedge. [Diagram 2] 2 is a schematic diagram of a flat magnetic metal particle in the magnetic wedge of the first embodiment. FIG. [Diagram 3] 4 is a conceptual diagram showing an example of a method for determining the thickness of a flat magnetic metal particle in the magnetic wedge of the first embodiment. FIG. [Figure 4] 2 is a conceptual diagram for explaining how to determine the maximum length and minimum length within the flat surface of a flat magnetic metal particle in the magnetic wedge of the first embodiment. FIG. [Diagram 5] A conceptual diagram for explaining another example of how to determine the maximum length and minimum length within the flat surface of a flat magnetic metal particle in the magnetic wedge of the first embodiment. [Figure 6] 1 is a schematic diagram showing the direction in which the coercive force of a magnetic wedge according to a first embodiment was measured, changing direction every 22.5 degrees relative to an angle of 360 degrees within the flat surface of a flat magnetic metal particle. FIG. [Figure 7] FIG. 2 is a schematic diagram of a magnetic wedge according to the first embodiment. [Figure 8] FIG. 2 is a schematic diagram of a magnetic wedge according to the first embodiment. [Figure 9] FIG. 4 is another schematic diagram of the magnetic wedge according to the first embodiment. [Figure 10] FIG. 6 is a schematic diagram showing an example of a radial gap type rotating electric machine according to a second embodiment. [Figure 11] FIG. 6 is a schematic diagram showing an example of an axial gap type rotating electric machine according to a second embodiment. [Figure 12] FIG. 6 is a schematic diagram showing an example of a generator according to a second embodiment. [Figure 13] FIG. 6 is a schematic diagram illustrating an example of a linear motor according to a second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, the embodiments will be described with reference to the drawings. In the drawings, the same or similar parts are denoted by the same or similar reference numerals. In this specification, unless otherwise specified, measurements are performed at 25°C.
[0009] In this specification, the "axial direction," "rotational direction," and "radial direction" are defined based on the rotor of the rotating electric machine. That is, the "axial direction" refers to the direction along the rotational axis of the rotor, the "rotational direction" refers to the circumferential direction around the rotational axis of the rotor (or the tangential direction thereof), and the "radial direction" refers to the direction perpendicular to (perpendicular to) the rotational axis of the rotor.
[0010] (First embodiment) The magnetic wedge of the embodiment is a magnetic wedge for a rotating electric machine, and the magnetic wedge is a magnetic wedge that includes a plurality of flat magnetic metal particles, an intervening phase, and has a surface coating layer on at least a portion of the surface of the magnetic wedge.
[0011] The flat magnetic metal particles are flaky particles having a flaky shape. The flat magnetic metal particles can be replaced with magnetic metal particles of any shape other than flat. The magnetic wedge of the present embodiment exerts its effect by covering at least a portion of the surface of the magnetic wedge with a surface coating layer. Therefore, magnetic metal particles having shapes other than flat can also exert excellent magnetic properties, electrical properties, and thermomechanical properties. In particular, when the particles have a flat shape, more excellent improvements in magnetic properties, electrical properties, and thermomechanical properties can be expected.
[0012] 2 is a schematic diagram of a flat magnetic metal particle in the magnetic wedge of the first embodiment, showing a coating layer 9 and a flat magnetic metal particle 10.
[0013] It is more preferable that the coating layer contains at least one non-magnetic metal selected from the group consisting of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, Ba, Sr, Cr, Mo, Ag, Ga, Sc, V, Y, Nb, Pb, Cu, In, Sn, and rare earth elements, and contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N), and fluorine (F).
[0014] As the non-magnetic metal, Al and Si are particularly preferred from the viewpoint of thermal stability. When the flat magnetic metal particles contain at least one non-magnetic metal selected from the group consisting of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, Ba, Sr, Cr, Mo, Ag, Ga, Sc, V, Y, Nb, Pb, Cu, In, Sn, and rare earth elements, it is more preferred that the coating layer contains at least one non-magnetic metal that is the same as the non-magnetic metal that is one of the components of the flat magnetic metal particles.
[0015] Of oxygen (O), carbon (C), nitrogen (N) and fluorine (F), it is preferable that the material contains oxygen (O), and it is preferable that the material is in the form of an oxide or a composite oxide.
[0016] The above is from the viewpoint of ease of forming the coating layer, oxidation resistance, and thermal stability. As a result, the adhesion between the flat magnetic metal particles and the coating layer can be improved, and the thermal stability and oxidation resistance of the magnetic wedge described below can be improved. The coating layer can not only improve the thermal stability and oxidation resistance of the flat magnetic metal particles, but also improve the electrical resistance of the flat magnetic metal particles. By increasing the electrical resistance, it is possible to suppress eddy current loss and improve the frequency characteristics of magnetic permeability. For this reason, it is preferable that the coating layer has high electrical resistance, for example, a resistance value of 1 mΩ·cm or more.
[0017] The presence of the coating layer is also preferable from a magnetic point of view. The flat magnetic metal particles can be regarded as a pseudo-thin film because the thickness of the flat magnetic metal particles is small compared to the size of the flat surface. In this case, the coating layer formed on the surface of the flat magnetic metal particles and integrated can be regarded as a pseudo-laminated thin film structure, so the magnetic domain structure is energetically stabilized. This makes it possible to reduce the coercive force and thus reduce the hysteresis loss, which is preferable. In this case, the magnetic permeability is also increased, which is preferable. From this point of view, it is more preferable that the coating layer is nonmagnetic, since this makes it easier to stabilize the magnetic domain structure.
[0018] The thickness of the coating layer is preferably 0.1 nm or more and 1 μm or less. By setting the thickness in this range, it is possible to suppress the decrease in magnetic permeability without making the saturation magnetization too small while maintaining appropriate thermal stability, oxidation resistance, and electrical resistance. Also, from a magnetic standpoint, the effect of stabilizing the magnetic domain structure to achieve low coercive force, low loss, and high magnetic permeability is not lost. The thickness of the coating layer is more preferably 0.1 nm or more and 100 μm or less.
[0019] The thickness of the flat magnetic metal particle refers to the average thickness of one flat magnetic metal particle. The method for determining the thickness is not limited as long as it is a method that can determine the average thickness of one flat magnetic metal particle.
[0020] For example, a method may be used in which a cross section perpendicular to the flat surface of a flat magnetic metal particle is observed using a transmission electron microscope (TEM), a scanning electron microscope (SEM), or an optical microscope, and 10 or more arbitrary locations are selected in the direction within the flat surface on the observed cross section of the flat magnetic metal particle, the thickness at each selected location is measured, and the average value is adopted.
[0021] Alternatively, on the cross-section of the observed flat magnetic metal particle, 10 or more points are selected at equal intervals in the direction within the flat plane from one end to the other end (it is preferable not to select the end and the other end as these are special locations), the thickness is measured at each selected point, and the average value is taken.
[0022] Fig. 3 is a conceptual diagram showing an example of how to determine the thickness of a flat magnetic metal particle in the magnetic wedge of the first embodiment. Fig. 3 specifically shows how to determine the thickness in this case. Ten points are selected at equal intervals from one end to the other end in the direction within the flat surface (excluding the ends), and the thicknesses at each point are denoted as t1, t2, ..., t 10 Then, the thickness of the flat magnetic metal particle is (t1+t2+...+t 10 ) / 10. It is preferable to measure as many points as possible, since this allows obtaining average information. If the cross-sectional contour line is very uneven or has a rough surface, making it difficult to determine the average thickness as is, it is preferable to smooth the contour line with an average straight line or curve, as appropriate, before carrying out the above method.
[0023] Moreover, the average thickness refers to the average value of the thicknesses of a plurality of flat magnetic metal particles, and is to be distinguished from the simple "thickness" mentioned above.
[0024] When determining the average thickness, it is preferable to adopt an average value for 20 or more flat magnetic metal particles. In addition, it is preferable to adopt the average value for as many flat magnetic metal particles as possible, since average information can be obtained. In addition, if it is not possible to observe 20 or more flat magnetic metal particles, it is preferable to observe as many flat magnetic metal particles as possible and adopt the average value for them.
[0025] The average thickness of the flat magnetic metal particles is preferably 10 nm to 100 μm, more preferably 10 nm to 1 μm, and even more preferably 10 nm to 100 nm. In addition, the flat magnetic metal particles preferably include those having a thickness of 10 nm to 100 μm, more preferably 10 nm to 1 μm, and even more preferably 10 nm to 100 nm. These are preferable because they can sufficiently reduce eddy current loss when a magnetic field is applied in a direction parallel to the flat surface. Also, a smaller thickness is preferable because the magnetic moment is confined in a direction parallel to the flat surface, and magnetization progresses more easily by rotational magnetization. When magnetization progresses by rotational magnetization, the magnetization tends to progress reversibly, so the coercive force is small, which is preferable because hysteresis loss can be reduced.
[0026] The average length of a flat magnetic metal particle is defined as (a+b) / 2, where a is the maximum length within the flat surface and b is the minimum length. The maximum length a and minimum length b can be calculated as follows. For example, consider the rectangle with the smallest area among the rectangles circumscribing the flat surface. Then, the length of the long side of that rectangle is the maximum length a, and the length of the short side is the minimum length b.
[0027] Fig. 4 is a conceptual diagram for explaining how to determine the maximum length and minimum length within the flat surface of a flat magnetic metal particle in the magnetic wedge of the first embodiment. Fig. 4 is a schematic diagram showing the maximum length a and minimum length b determined by the above method using several flat magnetic metal particles as examples. The maximum length a and minimum length b, like the average thickness, can be determined by observing the flat magnetic metal particle with a TEM, SEM, optical microscope, or the like.
[0028] It is also possible to perform image analysis of the micrograph on a computer to determine the maximum length a and the minimum length b. In either case, it is preferable to perform the determination on 20 or more flat magnetic metal particles. It is also preferable to perform the determination on as many flat magnetic metal particles as possible, since this allows the acquisition of average information.
[0029] In addition, when it is not possible to observe 20 or more flat magnetic metal particles, it is preferable to observe as many flat magnetic metal particles as possible and adopt the average value for them. In addition, since it is preferable to obtain an average value as much as possible, it is preferable to perform observation or image analysis in a state where the flat magnetic metal particles are uniformly dispersed (a state where multiple flat magnetic metal particles with different maximum and minimum lengths are dispersed as randomly as possible). For example, it is preferable to perform observation or image analysis by thoroughly mixing multiple flat magnetic metal particles and pasting them on a tape, or dropping multiple flat magnetic metal particles from above and pasting them on a tape.
[0030] However, depending on the flat magnetic metal particle, when the maximum length a and the minimum length b are obtained by the above method, the method may not capture the essence. Figure 5 is a conceptual diagram for explaining another example of a method for obtaining the maximum length and the minimum length in the flat surface of the flat magnetic metal particle in the magnetic wedge of the first embodiment.
[0031] For example, in the case of FIG. 5, the flat magnetic metal particle is elongated and curved, and in this case, essentially, the maximum length and minimum length of the flat magnetic metal particle are the lengths a and b shown in FIG. 5. Thus, the method of determining the maximum length a and b is not completely unique, and basically, it is fine to "consider the rectangle with the smallest area among the rectangles circumscribing the flat surface, and set the length of the long side of that rectangle as the maximum length a and the length of the short side as the minimum length b." However, depending on the shape of the particle, if this method does not capture the essence, the maximum length a and minimum length b that capture the essence can be determined flexibly. The thickness t is defined as the length perpendicular to the flat surface. The ratio A of the average length within the flat surface to the thickness is defined as A=((a+b) / 2) / t, using the maximum length a, the minimum length b, and the thickness t.
[0032] The average ratio of the average length within the flat surface to the thickness of the flat magnetic metal particles is preferably 5 to 10,000. This is because it increases the magnetic permeability. In addition, it is because it is possible to increase the ferromagnetic resonance frequency and therefore reduce the ferromagnetic resonance loss.
[0033] The average value is used for the ratio of the average length in the flat surface to the thickness. It is preferable to use an average value for 20 or more flat magnetic metal particles. It is also preferable to obtain average information by targeting as many flat magnetic metal particles as possible. If it is not possible to observe 20 or more flat magnetic metal particles, it is preferable to observe as many flat magnetic metal particles as possible and use the average value for them. For example, when there are particles Pa, particles Pb, and particles Pc, and their respective thicknesses Ta, Tb, and Tc and their average lengths in the flat surface La, Lb, and Lc are given, the average thickness is calculated as (Ta+Tb+Tc) / 3, and the average value of the ratio of the average length in the flat surface to the thickness is calculated as (La / Ta+Lb / Tb+Lc / Tc) / 3.
[0034] The flat magnetic metal particles preferably have a coercive force difference depending on the direction in the flat plane. The larger the ratio of the coercive force difference depending on the direction, the more preferable, and it is preferably 1% or more. More preferably, the ratio of the coercive force difference is 10% or more, even more preferably, the ratio of the coercive force difference is 50% or more, and even more preferably, the ratio of the coercive force difference is 100% or more.
[0035] The coercivity difference ratio here is defined as (Hc(max)-Hc(min)) / Hc(min) x 100(%), where Hc(max) is the maximum coercivity and Hc(min) is the minimum coercivity within the flat surface. Coercivity can be evaluated using a vibrating sample magnetometer (VSM) or similar. When the coercivity is low, a low magnetic field unit can be used to measure coercivity of 0.1 Oe or less. Measurements are performed by changing the direction within the flat surface relative to the direction of the measurement magnetic field.
[0036] In addition, "having a coercive force difference" means that when a magnetic field is applied in the 360-degree direction in the flat surface and the coercive force is measured, there is a direction in which the coercive force is maximum and a direction in which the coercive force is minimum. For example, when the coercive force is measured by changing the direction every 22.5 degrees with respect to an angle of 360 degrees in the flat surface, if a coercive force difference appears, that is, an angle where the coercive force is greater and an angle where the coercive force is smaller appear, it is considered to have a coercive force difference. FIG. 6 is a schematic diagram showing the direction when the coercive force is measured by changing the direction every 22.5 degrees with respect to an angle of 360 degrees in the flat surface of the flat magnetic metal particle in the magnetic wedge of the first embodiment. In addition, in FIG. 6, the flat surface of the flat magnetic metal particle is illustrated as being seen from above.
[0037] By having a coercivity difference within the flat plane, the minimum coercivity value is smaller than in the case of isotropy where there is almost no coercivity difference, which is preferable. In a material having magnetic anisotropy within the flat plane, the coercivity differs depending on the direction within the flat plane, and the minimum coercivity value is smaller than in a magnetically isotropic material. This reduces hysteresis loss and improves magnetic permeability, which is preferable. In FIG. 6, a flat magnetic metal particle 10 and a flat plane 6 are shown.
[0038] The flat magnetic metal particles also have a magnetic metal phase containing at least one first element selected from the group consisting of Fe, Co, and Ni. The flat magnetic metal particles contain Fe and Co, and the amount of Co is preferably 10 atomic % or more and 60 atomic % or less relative to the total amount of Fe and Co, and more preferably 10 atomic % or more and 40 atomic % or less. This is preferable because it is easy to impart a moderately large magnetic anisotropy and improves the above-mentioned magnetic properties. In addition, the Fe-Co system is preferable because it is easy to realize high saturation magnetization. Furthermore, it is preferable that the composition range of Fe and Co falls within the above range, because a higher saturation magnetization can be realized.
[0039] The elements can be easily analyzed by EDX (Energy Dispersive X-ray spectroscopy) or ICP (Inductively Coupled Plasma) optical emission spectroscopy.
[0040] The flat magnetic metal particles preferably contain at least one non-magnetic metal selected from the group consisting of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, Ba, Sr, Cr, Mo, Ag, Ga, Sc, V, Y, Nb, Pb, Cu, In, Sn, and rare earth elements. This can improve the thermal stability and oxidation resistance of the flat magnetic metal particles. Among them, Al and Si are particularly preferred because they are easily dissolved in Fe, Co, and Ni, which are the main components of the flat magnetic metal particles, and contribute to improving the thermal stability and oxidation resistance.
[0041] In addition, in order to induce magnetic anisotropy, there is also a method of making the crystallinity of the flat magnetic metal particles as amorphous as possible, and inducing magnetic anisotropy in one direction in the plane by a magnetic field or distortion. In this case, it is desirable to make the composition of the flat magnetic metal particles as easy to make amorphous as possible. From this point of view, it is preferable that the magnetic metal contained in the flat magnetic metal particles contains at least one additive element selected from B (boron), Si (silicon), Al (aluminum), C (carbon), Ti (titanium), Zr (zirconium), Hf (hafnium), Nb (niobium), Ta (tantalum), Mo (molybdenum), Cr (chromium), Cu (copper), W (tungsten), P (phosphorus), N (nitrogen), Ga (gallium), and Y (yttrium).
[0042] The additive element is preferably one that has a large difference in atomic radius from at least one first element selected from the group consisting of Fe, Co, and Ni. In addition, the additive element is preferably one that has a large negative mixing enthalpy between at least one first element selected from the group consisting of Fe, Co, and Ni and the additive element. In addition, it is preferable that the additive element is a multi-element system consisting of a total of three or more elements, including the first element and the additive element. In addition, semimetallic additive elements such as B and Si have a slow crystallization rate and are easily amorphized, so it is advantageous to mix them into the system.
[0043] From the above viewpoints, B, Si, P, Ti, Zr, Hf, Nb, Y, Cu, etc. are preferable, and among them, it is more preferable that the additive element contains one of B, Si, Zr, Hf, and Y. For example, it is preferable that the first element of the magnetic metal phase contains Fe and Co, and the additive element contains Si and B.
[0044] The total amount of the additional elements is preferably 0.001 at% or more and 80 at% or less with respect to the total amount of the first element and the additional elements, more preferably 5 at% or more and 80 at% or less, and further preferably 10 at% or more and 40 at% or less. In addition, the larger the total amount of the added elements, the more the amorphous state progresses and the easier it is to impart magnetic anisotropy, which is preferable (i.e., it is preferable from the viewpoint of low loss and high magnetic permeability), but on the other hand, it is not preferable because the proportion of the magnetic metal phase decreases, which reduces the saturation magnetization. For the above reasons, it is important to select the composition and the amount of added elements by comprehensively considering high saturation magnetization, low loss, high magnetic permeability, etc.
[0045] The intervening phase contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F). This is because it is possible to increase the electrical resistance. The electrical resistivity of the intervening phase is preferably higher than that of the flat magnetic metal particles. This is because it is possible to reduce the eddy current loss of the flat magnetic metal particles. Since the intervening phase exists surrounding the flat magnetic metal particles, it is preferable that it can improve the oxidation resistance and thermal stability of the flat magnetic metal particles. Among these, those containing oxygen are more preferable from the viewpoint of high oxidation resistance and high thermal stability. Since the intervening phase also plays a role of mechanically bonding the flat magnetic metal particles together, it is also preferable from the viewpoint of high strength.
[0046] The intervening phase preferably contains a resin, such as a thermoplastic resin, a thermosetting resin, a polyester resin, a vinyl ester resin, a polyethylene resin, a polystyrene resin, a polyvinyl chloride resin, a polyvinyl butyral resin, a polyvinyl alcohol resin, a polybutadiene resin, a Teflon (registered trademark) resin, a polyurethane resin, a cellulose resin, an ABS resin, a nitrile-butadiene rubber, a styrene-butadiene rubber, a silicone resin, other synthetic rubber, a natural rubber, an epoxy resin, a phenol resin, an allyl resin, a polybenzimidazole resin, an amide resin, a polyimide resin, a polyamideimide resin, a bismaleimide resin, or a copolymer thereof.
[0047] In particular, in order to realize high thermal stability, it is preferable that the intervening phase contains a silicone resin, a polyimide resin, an imide resin, or a bismaleimide resin, which have high heat resistance. Epoxy resins, phenolic resins, and polyester resins are generally used resins that have relatively high heat resistance and high strength, and are therefore preferable.
[0048] The intervening phase preferably contains at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenolic resins, epoxy resins, and silicone resins.The weight increase rate after exposure to air at 120°C for 30 minutes and then to room temperature for one week is preferably 1% or less, and more preferably 0.1% or less.
[0049] In addition, the resin contained in the intervening phase preferably has a water absorption rate of 1% or less, more preferably 0.1% or less, as defined by ISO 62:1999 (JIS K7209:2000). In order to increase strength, the intervening phase preferably also contains a material such as FRP (Fiber-Reinforced Plastics) that is a mixture of fibers such as glass fiber, aramid fiber, carbon fiber, Zylon fiber, polyethylene fiber, and boron fiber. As a result, the bond between the flat magnetic metal particles and the intervening phase becomes stronger, and mechanical properties such as thermal stability, strength, and toughness are easily improved.
[0050] The intervening phase surrounds the flat magnetic particles, which is preferable because it has excellent oxidation resistance and is less susceptible to deterioration of magnetic properties due to oxidation of the flat magnetic metal particles. The type of resin can be identified by IR (Infrared Spectroscopy), NMR (Nuclear Magnetic Resonance), etc.
[0051] Bismaleimide resins are preferred because the molding temperature can be kept relatively low (for example, 180°C or lower), and therefore molding can be performed using a general-purpose low-temperature hot press device. In addition, they are preferred because they can achieve high thermal stability and excellent mechanical properties after molding. Furthermore, they are easily composited (bonded) with flat magnetic metal particles, and are preferred because they can easily achieve excellent properties in terms of thermal stability as a composite material and mechanical properties such as strength and toughness. In addition, they are preferred because the intervening phase easily surrounds the flat magnetic particles, and deterioration of the magnetic properties due to oxidation of the flat magnetic metal particles is unlikely to occur.
[0052] The bismaleimide resin preferably has a glass transition temperature of 250° C. or higher, which is preferable because it provides high thermal stability and strength.
[0053] Specifically, the bismaleimide resins include 4,4'-diphenylmethane bismaleimide, phenylmethane maleimide, m-phenylene bismaleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 1,6'-bismaleimide-(2,2,4-trimethyl)hexane, 2,2'-diallyl bisphenol A, 4,4'-diphenyl It is preferable that the monomer contains aryl ether bismaleimide, 4,4'-diphenylsulfone bismaleimide, 1,3-bis(3-maleimidophenoxy)benzene, 1,3-bis(4-maleimidophenoxy)benzene, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 2,2'-bis[4-(4-maleimidophenoxy)phenyl]propane, etc. (These monomers are polymerized to produce bismaleimide resins, so it is preferable to contain the above as monomers.) This increases the thermal stability and strength, etc., and is therefore preferable.
[0054] In addition, the curing agent for curing the monomer preferably includes 4,4'-diaminodiphenylmethane, diaminodiphenyl ether, diaminodiphenyl sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, o,o'-diallyl bisphenol A, etc. However, the curing agent may be of any other type as long as it can appropriately cure the monomer.
[0055] A preferred combination of monomer and curing agent is, for example, 4,4'-diphenylmethane bismaleimide and 4,4'-diaminodiphenylmethane. In addition, when 4,4'-diphenylmethane bismaleimide and 4,4'-diaminodiphenylmethane are contained, the ratio of 4,4'-diphenylmethane bismaleimide to 4,4'-diaminodiphenylmethane is preferably 1 to 3, more preferably about 2. By having the above ratio, thermal stability and strength are increased, which is preferable.
[0056] The molecular weight of the intervening phase is preferably from 100 to 1000. This is preferable because it increases the thermal stability and strength.
[0057] The polyimide resin preferably contains a repeating unit represented by the following chemical formula (1). [ka] (1) In the chemical formula (1), R preferably contains any one of a biphenyl, triphenyl, and tetraphenyl structure, and R' preferably represents a structure having at least one aromatic ring therein.
[0058] Moreover, the polyimide resin more preferably has the following structural formula (2) or (3). [ka] (2) [ka] (3)
[0059] Fig. 7 is a schematic diagram of a magnetic wedge according to this embodiment. As shown in Fig. 7, the magnetic wedge may have not only a simple rectangular parallelepiped shape (with a rectangular cross section), but also various other shapes such as a trapezoid, hexagon, or convex cross section. The closer the magnetic wedge is positioned to the gap surface between the rotor and stator, the greater the improvement in efficiency of the rotating electric machine. From this viewpoint, the trapezoid, convex, and hexagonal shapes are more preferable than the rectangular shape.
[0060] Also, from the viewpoint of "a shape that easily draws the magnetic flux toward the magnetic wedge side, which tends to improve the efficiency of a rotating electric machine," the trapezoidal and convex shapes are more preferable than the hexagonal shape. On the other hand, from the viewpoint of ease of manufacture and high reliability of the mechanical properties and thermal properties of the material, the rectangular shape is most preferable, followed by the trapezoidal and hexagonal shapes. In this sense, the trapezoidal shape is very preferable because it is easy to arrange close to the gap surface between the rotor and the stator, and the trapezoidal shape makes it easy to draw the magnetic flux toward the magnetic wedge side, and furthermore, it is easy to manufacture and has high reliability of the mechanical properties and thermal properties of the material.
[0061] Regardless of the shape, the three axial directions that intersect perpendicularly or orthogonally to each other are defined as the width direction, thickness direction, and longitudinal direction. The longitudinal direction of a magnetic wedge is the direction in which the length of the magnetic wedge is longer. For example, when the shape of the magnetic wedge is a substantially rectangular parallelepiped, the direction along the longest side of the substantially rectangular parallelepiped shape is determined as the longitudinal direction of the magnetic wedge.
[0062] The thickness direction and width direction of the magnetic wedge are directions perpendicular to the longitudinal direction of the magnetic wedge. The thickness direction and width direction of the magnetic wedge can be distinguished as follows. When the target magnetic wedge is installed inside a rotating electric machine, the target magnetic wedge is removed from the inside of the rotating electric machine. Here, the rotation direction of the rotating electric machine becomes the width direction of the target magnetic wedge.
[0063] The thickness direction is perpendicular to the width direction. On the other hand, if the target magnetic wedge is not installed inside a rotating electric machine, the direction closest to the average orientation direction of the flat magnetic metal particles at the center of the cross section perpendicular to the longitudinal direction is the width direction. The thickness direction is perpendicular to the width direction. Note that, for the cross section perpendicular to the longitudinal direction, the end face of the target magnetic wedge is avoided.
[0064] For such a cross section, the target magnetic wedge is cut perpendicular to the longitudinal direction of the target magnetic wedge so that the cross section has a length of at least one tenth of the longitudinal length of the target magnetic wedge. In addition, as the central portion of the cross section formed by cutting, for example, a region containing a plurality of flat magnetic metal particles at the geometric center of the cross section is used. Next, the cross section formed by cutting the target magnetic wedge is observed using an optical microscope, SEM, or TEM.
[0065] Then, for each flat magnetic metal particle observed on the cross section formed by cutting, the rectangle with the smallest area among the rectangles circumscribing each flat magnetic metal particle is considered, and the direction of the long side of that rectangle is measured as the orientation direction.
[0066] However, some flat magnetic metal particles have unclear particle contours during observation, making them difficult to evaluate. In other words, there are cases where the particle contours cannot be clearly identified through image analysis, and in such cases, they are excluded from observation.
[0067] Fig. 8 is a schematic diagram of the magnetic wedge of this embodiment. In Fig. 8, the magnetic wedge has at least a surface coating layer present in part. By covering the surface of the magnetic wedge with the surface coating layer in this way, it is preferable because it has, for example, excellent magnetic properties and electric properties (high electrical resistivity, etc.), and furthermore, it is possible to maintain excellent properties without deteriorating the strength after a heat resistance test and the efficiency as a rotating electric machine. By having a surface coating layer, it is preferable because it is possible to suppress oxidation of the flat magnetic metal particles and flat magnetic metal surface particles contained in the magnetic wedge, and it is possible to maintain excellent magnetic properties (saturation magnetization, coercive force, magnetic permeability).
[0068] The magnetic wedge according to this embodiment may have a smooth or rough surface that contacts the surface coating layer. The rough surface that contacts the surface coating layer means that the surface has irregularities (rough surface), that the flat magnetic metal surface particles that exist near the surface that contacts the surface coating layer include those that are not oriented in the width direction, or that the flat magnetic metal surface particles are arranged with a part of their length on the outside (i.e., on the surface coating layer side) from the contour mean line.
[0069] FIG. 9 is another schematic diagram of the magnetic wedge of the present embodiment. In FIG. 9, a part of the flat magnetic metal particle included in the magnetic wedge has a part protruding from the magnetic wedge. In a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction (hereinafter, the characteristics are defined for this cross section), the flat magnetic metal particle existing near the widthwise contour line is shown. In addition, as a method for obtaining the cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, any method can be used as long as it can obtain the size and contour line of the flat magnetic metal particle. For example, the observation is performed with a scanning electron microscope (SEM: Scanning Electron Microscopy), an optical microscope, or a transmission electron microscope (TEM: Transmission Electron Microscopy), and the like, and the observation is performed at any magnification. Here, the flat magnetic metal particle existing closest to the widthwise contour line is referred to as a flat magnetic metal surface particle. In addition, the widthwise contour average line is an average line obtained by averaging the unevenness of the widthwise contour line. The contour mean line can be defined, for example, as the "mean line" in the surface roughness measurement of JIS-B0601 (ISO-4287).
[0070] In the magnetic wedge of the present embodiment, it is preferable that the flat magnetic metal surface particles are arranged outside the average contour line in the width direction, with 10% or more of the length of the flat magnetic metal particles.More preferably, the flat magnetic metal surface particles arranged outside the average contour line in the width direction of the magnetic wedge with 10% or more of the length are preferably included in the total number of flat magnetic metal surface particles present in the measured cross section from 1% to 90%, more preferably from 5% to 60%, and even more preferably from 5% to 30%.
[0071] The orientation angle of the flat magnetic metal surface particles, of which 10% or more of their length is positioned outside the widthwise contour average line of the magnetic wedge, is preferably 1 degree or more and 60 degrees or less with respect to the widthwise contour average line, more preferably 3 degrees or more and 45 degrees or less, and even more preferably 3 degrees or more and 30 degrees or less.
[0072] The surface roughness Ra of the widthwise contour of the magnetic wedge in Figures 8 and 9 is 0.1 μm to 100 μm, more preferably 0.1 μm to 10 μm, and even more preferably 1 μm to 10 μm. It is preferable that the widthwise contour (i.e., the surface in the width direction) in the cross section perpendicular to the longitudinal direction of the magnetic wedge at the center of the longitudinal direction meets this surface roughness range, but it is more preferable that the surface of the magnetic wedge including the width and length directions meets this surface roughness range, and even more preferably, any surface of the magnetic wedge meets this surface roughness range. The surface roughness Ra and its measurement method are defined in JIS-B0601 (ISO-4287).
[0073] When at least a part of the surface of the magnetic wedge has a portion where the flat magnetic metal particles protrude to the outside, the thickness of the surface coating layer is preferably equal to or greater than the average thickness of the flat magnetic metal surface particles, and more preferably equal to or greater than the average length of the flat magnetic metal particles. More preferably, it is equal to or greater than the maximum length of the flat magnetic metal particles. By having the above structure, the surface coating layer is preferably firmly adhered (bonded) to the magnetic wedge (anchor ring effect) and can protect the magnetic wedge. This is preferable because it improves the reliability of the material. For example, it is preferable because it can significantly improve the electrical resistivity, so that when used as a magnetic wedge, it can suppress electrical short circuits, reduce eddy current losses, and improve the efficiency of a rotating electric machine. It is also preferable because it can maintain excellent characteristics without deteriorating the strength after a heat resistance test and the efficiency of the rotating electric machine. It is also preferable because it can suppress oxidation of the flat magnetic metal particles and the flat magnetic metal surface particles, and can maintain excellent magnetic characteristics (saturation magnetization, coercive force, and magnetic permeability). Furthermore, by having the above-mentioned structure (the arrangement structure, number ratio, orientation angle, surface roughness, etc. of the flat magnetic metal surface particles), the magnetic flux can be efficiently guided in the rotating electric machine, which is preferable because it improves the magnetic permeability and the efficiency of the rotating electric machine. Regarding the magnetic permeability, it is preferable because it improves the magnetic permeability in the direction midway between the width direction and the thickness direction of the magnetic wedge. Also, in the direction midway between the width direction and the thickness direction of the magnetic wedge, the loss is lowered, which is preferable.
[0074] The surface coating layer preferably contains an inorganic material such as an oxide, a carbide, a nitride, or a boride, or an organic material such as a resin, and more preferably contains a resin.
[0075] The resin may be a thermoplastic resin, a thermosetting resin, a polyester resin, a vinyl ester resin, a polyethylene resin, a polystyrene resin, a polyvinyl chloride resin, a polyvinyl butyral resin, a polyvinyl alcohol resin, a polybutadiene resin, a Teflon (registered trademark) resin, a polyurethane resin, a cellulose resin, an ABS resin, a nitrile-butadiene rubber, a styrene-butadiene rubber, a silicone resin, other synthetic rubber, a natural rubber, an epoxy resin, a phenolic resin, an allyl resin, a polybenzimidazole resin, an amide resin, a polyimide resin, a polyamideimide resin, a bismaleimide resin, or a copolymer thereof.
[0076] In particular, in order to realize high thermal stability, it is preferable that the surface coating layer contains a silicone resin, a polyimide resin, an imide resin, or a bismaleimide resin, which have high heat resistance. Epoxy resin, phenol resin, and polyester resin are generally used resins that have relatively high heat resistance and high strength, and are therefore preferable.
[0077] The surface coating layer preferably contains at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenol resins, epoxy resins, and silicone resins.
[0078] As mentioned above, the type of resin can be identified by IR, NMR, etc. In addition, the surface coating layer is preferably a resin whose weight increase rate after exposure to air at 120°C for 30 minutes and then to room temperature for one week is 1% or less, more preferably 0.1% or less. In addition, the water absorption rate as defined by ISO 62:1999 (JIS K7209:2000) is preferably 1% or less, more preferably 0.1% or less.
[0079] A preliminary investigation revealed that in magnetic wedges consisting of flat magnetic metal particles and an intervening phase, especially when the intervening phase is resin, absorbing moisture or humidity increases the weight and is prone to deterioration of mechanical properties such as strength and thermomechanical properties. In addition, when flat magnetic metal particles absorb moisture or humidity, they also oxidize, decreasing the saturation magnetization and magnetic permeability and increasing losses, which is undesirable. Therefore, it is considered effective to prevent moisture or humidity from coming into contact with the intervening phase as much as possible (suppressing weight increase).
[0080] From the above, in this embodiment, by covering the surface of the magnetic wedge with a surface coating layer with low water absorption and hygroscopicity, it is possible to prevent water and moisture from coming into contact with the intervening phase as much as possible. Therefore, as described above, it is preferable that the surface coating layer is a resin whose weight increase rate after exposure to air at 120°C for 30 minutes and then to room temperature for one week is 1% or less, and more preferably 0.1% or less. In addition, it is preferable that the water absorption rate defined by ISO 62:1999 (JIS K7209:2000) is 1% or less, and more preferably 0.1% or less. More preferably, the surface coating layer contains at least one resin selected from the group consisting of bismaleimide resin, polyimide resin, polyester resin, phenolic resin, epoxy resin, and silicone resin, and has a weight gain of 1% or less after exposure to air at 120°C for 30 minutes and then at room temperature for 1 week, and has a water absorption rate of 1% or less as defined by ISO 62:1999 (JIS K7209:2000). Even more preferably, the surface coating layer contains at least one resin selected from the group consisting of bismaleimide resin, polyimide resin, polyester resin, phenolic resin, epoxy resin, and silicone resin, and has a weight gain of 0.1% or less after exposure to air at 120°C for 30 minutes and then at room temperature for 1 week, and has a water absorption rate of 0.1% or less as defined by ISO 62:1999 (JIS K7209:2000). By forming the above-mentioned surface coating layer, it is possible to maintain excellent properties without deteriorating mechanical properties such as strength and thermomechanical properties. In addition, since oxidation of the flat magnetic metal particles is suppressed, it is possible to maintain excellent properties without deteriorating saturation magnetization, magnetic permeability, and loss.
[0081] A method for manufacturing the magnetic wedge of this embodiment will be described below. Note that the manufacturing method is not particularly limited and will be described merely as an example.
[0082] The first step is a step of producing a magnetic metal ribbon containing at least one first element selected from the group consisting of Fe, Co, and Ni. This step is a step of producing a ribbon or a thin film using a film-forming device such as a roll quenching device or a sputtering device. In this case, in the film-forming method using the film-forming device, it is desirable to form a film that has uniaxial anisotropy in the film plane by film-forming in a magnetic field or rotational film-forming.
[0083] The second step is a step of heat treating the magnetic metal ribbon at a temperature of 50°C to 800°C. The heat treatment is preferably performed in a vacuum atmosphere with a low oxygen concentration, an inert atmosphere, or a reducing atmosphere, and more preferably in a reducing atmosphere such as H2 (hydrogen), CO (carbon monoxide), or CH4 (methane). It is more preferable to perform the heat treatment in a magnetic field.
[0084] The third step is to pulverize the heat-treated magnetic metal ribbon to produce flat magnetic metal particles. In this step, pulverization is performed using a pulverizing device such as a bead mill or a planetary mill. The pulverizing device can be of any type. Examples include a planetary mill, a bead mill, a rotary ball mill, a vibrating ball mill, an agitating ball mill (attritor), a jet mill, a centrifuge, or a combination of a mill and centrifugation.
[0085] In the third step, the thickness of the flat magnetic metal particles can be reduced by combining rolling with simple pulverization. If the desired thickness is achieved by the second step, the rolling process can be omitted. Here, rolling may be performed simultaneously, or after pulverization, or after rolling. In this case, a device capable of applying a strong gravitational acceleration is preferable, and for example, a planetary mill, a bead mill, a rotary ball mill, a vibrating ball mill, an agitating ball mill (attritor), a jet mill, a centrifuge, or a method combining a mill and centrifugation can be used.
[0086] It is desirable to carry out the above cutting, crushing and rolling (rolling is carried out as necessary, and not carried out if not necessary), and in some cases to repeat the cutting, crushing and rolling processes until the material becomes flat magnetic metal particles of the specified thickness and aspect ratio.
[0087] It is also preferable to remove the lattice distortion of the obtained flat magnetic metal particles by heat treatment. The heat treatment is preferably carried out at a temperature of 50°C to 800°C, as in the second step, and the heat treatment atmosphere is preferably a vacuum atmosphere with a low oxygen concentration, an inert atmosphere, or a reducing atmosphere, and more preferably a reducing atmosphere such as H2, CO, or CH4. It is more preferable to carry out the heat treatment in a magnetic field.
[0088] Next, in the fourth step, the above-mentioned intervening phase and magnetic metal particles are mixed to form a mixed powder of the intervening phase and flat magnetic metal particles. Next, in the fifth step, the mixed powder of the intervening phase and magnetic metal particles is molded. Also, heat treatment may be performed before or after the above steps as appropriate. That is, heat treatment may be performed before or after molding, or at the same time as molding. Also, heat treatment may be performed before or after processing. The heat treatment conditions are as described above. Also, it is more preferable to perform heat treatment in a magnetic field.
[0089] In the fifth step, it is preferable to use a method of applying a press pressure in a uniaxial direction, such as uniaxial press molding or hot press molding. When a press pressure is applied in a uniaxial direction, the flat magnetic metal particles tend to be layered and oriented in the direction of the press pressure application. Therefore, in a simple uniaxial press molding, the flat magnetic metal particles are layered and oriented in one direction in the direction of the press pressure application, which is not preferable. Therefore, when applying a press pressure in a uniaxial direction, it is preferable to apply a magnetic field in a direction parallel to the direction of the press pressure application. It is also preferable to magnetize the mold punch during molding in a direction parallel to the direction of the press pressure application. This makes it easier for the flat magnetic metal particles to move in a direction parallel to the direction of the press pressure application. It is also preferable to perform hot press molding after uniaxial press molding. When the intervening phase is, for example, a thermosetting resin, it is preferable to adjust the hot press temperature and time in hot press molding and stop before the intervening phase hardens. In addition, in hot press, it is more preferable to perform hot press while applying a magnetic field in a direction parallel to the direction of the press pressure application.
[0090] It is also preferable to reduce or release the pressing pressure when the resin is softened and melted during hot pressing. The hot pressing temperature is preferably 50°C or higher and 1000°C or lower, more preferably 50°C or higher and 800°C or lower. The stronger the applied magnetic field, the more preferable it is, but it is preferable to apply 1 kOe or more, more preferably 10 kOe or more. The pressing pressure is preferably 1 MPa or higher and 100 MPa or lower, more preferably 1 MPa or higher and 10 MPa or lower.
[0091] After that, it is preferable to perform heat treatment while applying a magnetic field in a direction parallel to the direction of application of the pressing pressure, and to completely harden the product. The heat treatment temperature is preferably 50° C. or higher and 1000° C. or lower, and more preferably 50° C. or higher and 800° C. or lower. The stronger the magnetic field to be applied, the better, but it is preferable to apply a magnetic field of 1 kOe or higher, and more preferably 10 kOe or higher.
[0092] Here, by adjusting the hot pressing temperature and time, it is possible to adjust the "ratio of the flat magnetic metal surface particles that are arranged outside the average contour line in the width direction of the magnetic wedge by 10% or more of their length to the total number of flat magnetic metal surface particles". For example, if you want to increase the "ratio of the flat magnetic metal surface particles that are arranged outside the average contour line in the width direction of the magnetic wedge by 10% or more of their length to the total number of flat magnetic metal surface particles", you can adjust it by lowering the hot pressing temperature or shortening the hot pressing time. Conversely, if you want to decrease the "ratio of the flat magnetic metal surface particles that are arranged outside the average contour line in the width direction of the magnetic wedge by 10% or more of their length to the total number of flat magnetic metal surface particles", you can adjust it by increasing the hot pressing temperature or lengthening the hot pressing time. Even if the intervening phase is a thermoplastic resin or an oxide having a softening point, it is possible to manufacture a similar magnetic wedge by devising a molding process. In other words, it is possible to manufacture a similar magnetic wedge regardless of the type of intervening phase. For example, when the resin is softened and melted during hot pressing, it is possible to manufacture a similar magnetic wedge by reducing or releasing the pressing pressure, or by applying a magnetic field parallel to the direction of the pressing pressure, and then lowering the temperature and solidifying it under that condition.
[0093] Next, in the sixth step, a surface coating layer is formed on the surface of the molded magnetic wedge. In this step, an inorganic material or an organic material is coated on the surface of the magnetic wedge. The coating method is not particularly limited. When coating an organic material such as a resin, it is preferable to coat the material by an impregnation method, a dipping method, or the like, or in some cases to press the material with a hot press after coating. When coating an inorganic material, it is preferable to coat the material by a gas phase method or a liquid phase method such as sol-gel, or in some cases to press the material with a hot press after coating. It is also preferable to perform a heat treatment after coating to form a strong coating layer.
[0094] When measuring the coercive force depending on the direction within a plane parallel to the flat surfaces of the flat magnetic metal particles of the magnetic wedge, for example, the coercive force is measured by changing the direction every 22.5 degrees over an angle of 360 degrees within the plane.
[0095] By having a coercivity difference in the plane of the magnetic wedge, the minimum coercivity value is smaller than in the case of isotropy where there is almost no coercivity difference, which is preferable. In a material having magnetic anisotropy in a plane, the coercivity differs depending on the direction in the plane, and the minimum coercivity value is smaller than in a magnetically isotropic material. This reduces hysteresis loss and improves magnetic permeability, which is preferable.
[0096] In a plane parallel to the flat surface of the flat magnetic metal particle of the magnetic wedge, the larger the ratio of the coercive force difference due to the direction, the more preferable, and it is preferably 1% or more. More preferably, the ratio of the coercive force difference is 10% or more, even more preferably, the ratio of the coercive force difference is 50% or more, and even more preferably, the ratio of the coercive force difference is 100% or more. The ratio of the coercive force difference here is defined as (Hc(max)-Hc(min)) / Hc(min)×100(%), using the maximum coercive force Hc(max) and the minimum coercive force Hc(min) in the flat surface.
[0097] The coercive force can be easily evaluated using a vibrating sample magnetometer (VSM) or the like. When the coercive force is low, a coercive force of 0.1 Oe or less can be measured by using a low magnetic field unit. The measurement is performed by changing the direction of the measuring magnetic field within the plane of the magnetic wedge (within a plane parallel to the flat surface of the flat magnetic metal particle).
[0098] When calculating the coercive force, the difference between the magnetic fields at the two points where the magnetization intersects the horizontal axis (magnetic fields H1 and H2 where magnetization is zero) can be divided by 2 (i.e., coercive force = |H2-H1| / 2).
[0099] As described above, according to the present embodiment, the magnetic wedge is a magnetic wedge for a rotating electric machine, and the magnetic wedge comprises a plurality of flat magnetic metal particles and an intervening phase, and a surface coating layer is present on at least a part of the surface of the magnetic wedge. This makes it possible to provide a magnetic wedge having excellent electrical properties, excellent heat resistance (electrical properties, magnetic properties, mechanical properties), etc. In addition, it is more preferable that the magnetic wedge has flat magnetic metal particles, and the flat magnetic metal particles have the above-mentioned structure (arrangement structure of the flat magnetic metal surface particles, number ratio, orientation angle, surface roughness, etc.), which is preferable because the magnetic flux can be efficiently guided in the rotating electric machine, and the magnetic permeability and efficiency of the rotating electric machine are improved. In addition, by having flat magnetic metal particles with the above-mentioned structure, the surface coating layer can be firmly formed (anchor ring effect), the reliability of the material is further improved, and even better heat resistance (electrical properties, magnetic properties, mechanical properties) can be realized, which is preferable.
[0100] (Second embodiment) The rotating electric machine of this embodiment includes the magnetic wedge of the first embodiment. Therefore, the description of the contents overlapping with the first embodiment will be omitted. In this specification, the rotating electric machine means a concept including any of an electric motor (motor), a generator, and a motor-generator that functions as both a motor and a generator as necessary.
[0101] FIG. 10 is an example of a radial gap type motor of this embodiment. The radial gap type motor has a rotor and a stator arranged to face the rotor with a predetermined gap in the radial direction. In FIG. 10, the rotor is arranged inside the stator, but it may be arranged outside. The rotor has a rotor core and a shaft, and is supported so as to be rotatable. On the other hand, the stator has a stator core, a field coil inserted in the slot of the stator core, and a magnetic wedge held in the wedge groove at the slot opening. FIG. 10 shows an example in which the magnetic wedge of the first embodiment is arranged, but is not limited to this. In the case of a radial gap type rotating electric machine, the stator is arranged to face the rotor with a predetermined gap in the radial direction, so that the "gap surface" is a surface parallel to a cylindrical surface centered on the rotation axis of the rotor. Therefore, the radial direction is perpendicular to the gap surface, and the axial direction and the rotation direction are parallel to the gap surface. In FIG. 10, flat magnetic metal particles 10, intervening phases 20, magnetic wedges 100, a rotating electric machine 200, a rotor 210, a stator 220, a coil 230, a gap surface 240, and iron core teeth 250 are shown.
[0102] By arranging the magnetic wedge of the first embodiment, it is possible to reduce harmonic loss occurring on the rotor surface while suppressing leakage magnetic flux. In addition, the magnetic flux passing through the air gap increases, so the torque of the radial gap motor is increased. High efficiency can be achieved by either or both of the above loss reduction effect and torque increase effect.
[0103] The radial gap motor may be one having a conductor in the rotor (induction motor), one having a permanent magnet (permanent magnet motor), or one having a magnetic body (reluctance motor).
[0104] FIG. 11 is an example of an axial gap motor of this embodiment. The axial gap motor has a rotor and a stator arranged to face the rotor with a predetermined gap in the axial direction, and the stator is provided with a stator core, a field coil inserted in a slot of the stator core, and a magnetic wedge held in a wedge groove at the slot opening. By arranging the magnetic wedge of this embodiment, it is possible to reduce harmonic loss generated on the rotor surface while suppressing an increase in leakage magnetic flux. In addition, since the magnetic flux passing through the gap increases, the torque of the axial gap motor is increased. As a result, high efficiency can be achieved. In FIG. 11, the rotor is arranged between two stators, but it may be arranged on one or both sides of one stator. In the case of an axial gap rotating electric machine, the stator is arranged to face the rotor with a predetermined gap in the axial direction, so the "gap surface" is a surface perpendicular to the rotation axis of the rotor. Therefore, the axial direction is perpendicular to the gap surface, and the rotation direction and the radial direction are parallel to the gap surface. In Fig. 12, flat magnetic metal particles 10, intervening phases 20, magnetic wedges 100, rotating electric machine 200, rotor 210, coil 230, gap surface 240, iron core teeth 250, stator 270, and shaft 280 are shown.
[0105] FIG. 12 is a schematic diagram showing an example of a generator of this embodiment. A generator usually has a rotor that houses an excitation coil in the slots of a rotor core (otherwise, a rotor using a permanent magnet as an excitation source may be adopted) and a stator that houses an armature coil in the slots of a stator core, and generates electric power in the armature coil by rotating the rotor and passing an excitation current through the excitation coil. The rotor includes a rotor core, a field coil inserted in the slots of the rotor core, and a magnetic wedge held in a wedge groove at the opening of the slot, and is supported by a bearing so as to be rotatable. By disposing the magnetic wedge of this embodiment, it is possible to reduce harmonic loss occurring on the surface of the stator while suppressing an increase in leakage magnetic flux. In addition, the magnetic flux that passes through the air gap and interlinks with the armature coil increases, so that the generated voltage induced in the armature coil increases. As a result, high efficiency can be achieved. In FIG. 12, the magnetic wedges are arranged at the slot openings of the rotor core, but they may be arranged at the slot openings of the stator core. In addition, the figure shows a winding type generator with an excitation coil in the rotor, but it may be a permanent magnet type generator with a permanent magnet in the rotor. In this case, the magnetic wedges are arranged at the slot openings of the stator core. In FIG. 12, the flat magnetic metal particles 10, the intervening phase 20, the magnetic wedges 100, the rotating electric machine 200, the rotor 210, the stator core 222, the excitation coil 232, the armature coil 234, the gap surface 240, and the core teeth 250 are shown.
[0106] Since a linear motor is a flat plate-shaped structure developed from a radial gap motor, the magnetic wedge of the present invention can be applied to the linear motor. That is, the stator may include a stator core and a field coil inserted into a slot of the stator core, and a magnetic wedge may be provided at the slot opening. FIG. 13 is a schematic diagram showing an example of a linear motor of this embodiment. In a linear motor, the moving direction of the mover, the direction perpendicular to the moving direction of the mover, and the direction perpendicular to the stator correspond to the rotation direction, axial direction, and radial direction of the radial gap motor, respectively. By disposing the magnetic wedge of this embodiment, it is possible to reduce harmonic loss generated on the surface of the mover while suppressing an increase in leakage flux. In addition, the magnetic flux passing through the gap increases, and thus the thrust of the linear motor is improved. As a result, high efficiency can be achieved. In FIG. 13, flat magnetic metal particles 10, intervening phases 20, magnetic wedges 100, a stator 220, a coil 230, a gap surface 240, iron core teeth 250, and a mover 290 are shown.
[0107] As described above, according to the rotating electric machine of this embodiment, the increase in leakage magnetic flux due to the use of magnetic wedges can be suppressed, and the pulsation of the magnetic flux distribution on the surface of the iron core can be effectively alleviated, thereby realizing high efficiency. Note that the slot shape of the rotating electric machine of this embodiment may be a semi-closed slot, but is preferably an open slot. In this case, harmonic loss can be significantly reduced, which is preferable.
[0108] The rotating electric machine of the present embodiment can be applied to transportation systems such as railways, electric vehicles, and hybrid cars, social systems such as elevators and air conditioners, industrial systems such as robots, pumps, compressors, and blowers, energy systems such as thermal power generators, hydroelectric generators, wind power generators, nuclear power generators, and geothermal generators, and home appliances such as washing machines, and can improve the efficiency of the system. In particular, in large-capacity industrial machines, an open slot is generally adopted as the slot shape, so it is preferable to include the magnetic wedge of the first embodiment. In addition, in main motors for railways, a form-wound coil is used because of the need to withstand high voltage and vibration, and an open slot is adopted as the slot shape, so it is preferable to include the magnetic wedge of the first embodiment.
[0109] In railways, the loss of rotating electric machines accounts for about half of the power consumption when the train is running, so the effect of improving efficiency by reducing the loss of rotating electric machines is large. Also, in electric vehicles and hybrid cars, the efficiency of the main motor can be improved by using the magnetic wedge of the first embodiment, so the driving range can be extended.
[0110] In the case of generators, the present invention is expected to be highly effective for hydroelectric generators, particularly variable speed pumped storage generators, and also for wind power generators.
[0111] (Example) Examples 1 to 15 will be described in more detail below in comparison with Comparative Example 1.
[0112] Example 1 First, a ribbon of Fe-Co-Si-B (Fe70Co30B25 (at%)-4wt%Si) is produced using a single roll quenching device. The ribbon obtained is then heat-treated at 300°C in an H2 atmosphere. Next, this ribbon is pulverized using a mixer device to obtain flat magnetic metal particles (the average thickness is about 15 μm, and the average ratio of the average length in the flat plane to the thickness is about 30). The flat magnetic metal particles obtained are then mixed with polyester-based resin and molded. Then, hot press molding is performed to completely harden the resin and produce a magnetic wedge. At this time, there were no flat magnetic metal surface particles whose length was more than 10% outside the average contour line in the width direction of the magnetic wedge. Then, a polyester-based resin was coated as a surface coating layer. It was confirmed that the thickness of the surface coating layer was greater than or equal to the average thickness of the flat magnetic metal surface particles, that the weight increase rate of the surface coating layer was 1% or less after exposure to air at 120°C for 30 minutes and then to room temperature for one week, and that the water absorption rate as defined by ISO 62:1999 (JIS K7209:2000) was 1% or less.
[0113] Example 2 The embodiment is almost the same as Example 1, except that the type of the surface coating layer is a bismaleimide resin.
[0114] Example 3 The embodiment is almost the same as the embodiment 1, except that the type of the surface coating layer is a polyimide resin.
[0115] Example 4 The embodiment is almost the same as Example 1, except that the type of the surface coating layer is a phenol-based resin.
[0116] Example 5 The embodiment is almost the same as Example 1, except that the surface coating layer is made of an epoxy resin.
[0117] Example 6 The embodiment is almost the same as Example 1, except that the type of the surface coating layer is a silicone-based resin.
[0118] Example 7 In Example 1, when the flat magnetic metal particles are mixed with the polyester resin and molded (when applying a press pressure in one axial direction), a magnetic field is applied in a direction parallel to the direction of application of the press pressure. Then, hot press molding is performed. In the hot press molding, the hot press temperature and time are adjusted, and the molding is stopped before hardening. Then, heat treatment is performed while applying a magnetic field in a direction parallel to the direction of application of the press pressure, and the magnetic wedge is completely hardened to produce a magnetic wedge. By adjusting the hot press temperature and time, the ratio of the flat magnetic metal surface particles that are arranged outside the average contour line in the width direction of the magnetic wedge for 10% or more of their length to the total number of flat magnetic metal surface particles was adjusted (30% in this Example 7). Then, a polyester resin was coated as a surface coating layer. It was confirmed that the thickness of the surface coating layer was greater than or equal to the average thickness of the flat magnetic metal surface particles, that the weight increase rate of the surface coating layer was 1% or less after exposure to air at 120°C for 30 minutes and then to room temperature for one week, and that the water absorption rate as defined by ISO 62:1999 (JIS K7209:2000) was 1% or less.
[0119] Example 8 The procedure is almost the same as in Example 7, except that the type of the surface coating layer was a bismaleimide resin.
[0120] Example 9 The embodiment is almost the same as Example 7, except that the type of the surface coating layer is a polyimide resin.
[0121] Example 10 The embodiment is almost the same as Example 7, except that the type of the surface coating layer is a phenol-based resin.
[0122] Example 11 The procedure is almost the same as in Example 7, except that the surface coating layer is made of an epoxy resin.
[0123] Example 12 The embodiment is almost the same as Example 7, except that the type of the surface coating layer is a silicone-based resin.
[0124] Example 13 This is almost the same as Example 7, except that by adjusting the hot pressing temperature and time, the proportion of flat magnetic metal surface particles whose length is more than 10% and which are positioned outside the average contour line in the width direction of the magnetic wedge is 1% of the total number of flat magnetic metal surface particles.
[0125] Example 14 This is almost the same as Example 7, except that by adjusting the hot pressing temperature and time, the proportion of flat magnetic metal surface particles whose length is more than 10% outside the average contour line of the magnetic wedge in the width direction to the total number of flat magnetic metal surface particles is set to 90%.
[0126] Example 15 This is almost the same as Example 7, except that by adjusting the hot pressing temperature and time, the proportion of flat magnetic metal surface particles whose length is more than 10% and which are positioned outside the average contour line in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles is set to 95%.
[0127] Comparative Example 1 The procedure is almost the same as in Example 1, except that the surface coating layer of polyester resin is not formed.
[0128] Table 1 shows, for the magnetic wedges of this embodiment (Examples 1 to 15), the presence / absence of a surface coating layer, the type of surface coating layer (only when a surface coating layer is present), and the ratio of flat magnetic metal surface particles whose length is 10% or more outside the average contour line in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles, along with Comparison Example 1.
[0129] Table 2 shows the electrical resistivity, electrical resistivity after heat resistance test, magnetic permeability, and strength of the magnetic wedge of this embodiment (Examples 1 to 15) together with Comparative Example 1.
[0130] (1) Electrical resistivity: The DC electrical resistivity was measured on the surface of the magnetic wedge in the length and width directions, and expressed as a ratio to the DC electrical resistivity of the sample of Comparative Example 1 (=DC electrical resistivity of evaluation sample / DC electrical resistivity of Comparative Example 1).
[0131] (2) Electrical resistivity after heat resistance test: For the evaluation sample, the DC electrical resistivity (DC electrical resistivity on the surface in the length and width directions of the magnetic wedge) was measured after heating in air at 180°C for 100 hours (heat resistance test), and is shown as a ratio to the DC electrical resistivity of the sample of Comparative Example 1 (=DC electrical resistivity of evaluation sample after heating in air at 180°C for 100 hours / DC electrical resistivity of Comparative Example 1 after heating in air at 180°C for 100 hours).
[0132] (3) Permeability after heat resistance test: The permeability (permeability at 100 Hz in the direction midway between the width and thickness directions of the magnetic wedge) of the evaluation sample was measured after heating in air at 180°C for 100 hours (heat resistance test), and is shown as a ratio to the permeability of the sample of Comparative Example 1 after heating in air at 180°C for 100 hours (=permeability of evaluation sample after heating in air at 180°C for 100 hours / permeability of Comparative Example 1 after heating in air at 180°C for 100 hours).
[0133] (4) Strength after heat resistance test: For the evaluation sample, the flexural strength was measured at 25°C after heating in air at 180°C for 100 hours (heat resistance test), and shown as a ratio to the flexural strength of the sample of Comparative Example 1 at 25°C after heating in air at 180°C for 100 hours (= flexural strength of evaluation sample at 25°C after heating in air at 180°C for 100 hours / flexural strength of Comparative Example 1 at 25°C after heating in air at 180°C for 100 hours).
[0134] [Table 1]
[0135] [Table 2]
[0136] From Table 2, it can be seen that, compared to Comparative Example 1, Examples 1 to 6 have excellent properties in terms of electrical resistivity, electrical resistivity after heat resistance test, magnetic permeability, and strength. This is because the formation of an insulating surface coating layer not only increases the electrical resistivity of the surface of the magnetic wedge, but also protects the magnetic wedge during the heat resistance test. As a result, it was found that excellent properties can be maintained without deteriorating the electrical resistivity, magnetic permeability, and strength after the heat resistance test. In addition, such an effect is more remarkable when the flat magnetic metal surface particles, the length of which is 10% or more of which is arranged outside the average contour line in the width direction of the magnetic wedge, are included in the magnetic wedge in a range of 1% to 90% of the total number of the flat magnetic metal surface particles. In Examples 7 to 14, the flat magnetic metal surface particles, which are arranged for 10% or more of their length outside the contour average line in the width direction of the magnetic wedge, are between 1% and 90% of the total number of flat magnetic metal surface particles, and this shows that higher characteristics can be achieved compared to the 0% in Examples 1 to 6 and the 95% in Example 15. In other words, it was found that the electrical resistivity, magnetic permeability, and strength after heat resistance testing are improved by "having between 1% and 90% of the total number of flat magnetic metal surface particles, which are arranged for 10% or more of their length outside the contour average line in the width direction of the magnetic wedge." To summarize, forming a surface coating layer increases the electrical resistivity, and also improves the electrical resistivity, magnetic permeability, and strength after heat resistance testing. It was found that the effect is particularly pronounced when "flat magnetic metal surface particles with 10% or more of their length positioned outside the average contour line in the width direction of the magnetic wedge account for 1% or more and 90% or less of the total number of flat magnetic metal surface particles."
[0137] Although some embodiments and examples of the present invention have been described, these embodiments and examples are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims.
[0138] The above-described embodiments can be summarized as the following technical solutions. (Technical proposal 1) A magnetic wedge for a rotating electric machine, the magnetic wedge comprising a plurality of flat magnetic metal particles and an intervening phase; A magnetic wedge having a surface coating layer on at least a portion of a surface of the magnetic wedge. (Technical proposal 2) A magnetic wedge according to technical solution 1, wherein the thickness of the surface coating layer is greater than or equal to the average thickness of the flat magnetic metal surface particles. (Technical proposal 3) A magnetic wedge according to technical proposal 1 or technical proposal 2, wherein the surface coating layer contains a resin. (Technical proposal 4) A magnetic wedge described in any one of Technical Schemes 1 to 3, wherein the surface coating layer is a resin whose weight increase rate after exposure to air at 120°C for 30 minutes and then to room temperature air for one week is 1% or less. (Technical proposal 5) A magnetic wedge according to any one of Technical Schemes 1 to 4, wherein the surface coating layer has a water absorption rate of 1% or less as defined by ISO 62:1999 (JIS K7209:2000). (Technical proposal 6) A magnetic wedge according to any one of Technical Schemes 1 to 5, wherein the surface coating layer contains at least one resin selected from the group consisting of bismaleimide-based resins, polyimide-based resins, polyester-based resins, phenol-based resins, epoxy-based resins, and silicone-based resins. (Technical proposal 7) In a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, A magnetic wedge described in any one of Technical Proposals 1 to 6, comprising flat magnetic metal surface particles among the plurality of flat magnetic metal particles, wherein 10% or more of the length of the flat magnetic metal particles is positioned outside the average contour line of the magnetic wedge in the width direction. (Technical proposal 8) A magnetic wedge described in any one of Technical Proposals 1 to 7, in which, in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, flat magnetic metal surface particles having 10% or more of their length positioned outside the average contour line of the width direction of the magnetic wedge account for 1% or more and 90% or less of the total number of flat magnetic metal surface particles. (Technical proposal 9) A magnetic wedge described in any one of Technical Proposals 1 to 8, wherein in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, the orientation angle of flat magnetic metal surface particles, which are arranged outside the widthwise contour average line of the magnetic wedge for more than 10% of their length, is greater than or equal to 1 degree and less than 60 degrees with respect to the widthwise contour average line. (Technical proposal 10) A magnetic wedge according to any one of technical proposals 1 to 9, wherein the surface roughness Ra of a widthwise contour line in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction is 0.1 μm or more and 100 μm or less. (Technical proposal 11) A magnetic wedge described in any one of Technical Proposals 1 to 10, wherein the intervening phase is present between the multiple flat magnetic metal particles and contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F). (Technical proposal 12) A magnetic wedge according to any one of technical proposals 1 to 11, wherein the intervening phase contains a resin. (Technical proposal 13) A magnetic wedge according to any one of Technical Schemes 1 to 12, wherein the intervening phase contains at least one resin selected from the group consisting of bismaleimide-based resins, polyimide-based resins, polyester-based resins, phenol-based resins, epoxy-based resins, and silicone-based resins. (Technical proposal 14) A magnetic wedge described in any one of Technical Proposals 1 to 13, wherein the plurality of flat magnetic metal particles have an average thickness of 10 nm or more and 100 μm or less, have a magnetic metal phase containing at least one first element selected from the group consisting of Fe, Co and Ni, and have an average ratio of the average length within the flat surface to the thickness of 5 or more and 10,000 or less. (Technical proposal 15) A magnetic wedge described in any one of Technical Proposals 1 to 14, wherein at least a portion of the surface of the flat magnetic metal particle is covered with a coating layer having a thickness of 0.1 nm or more and 1 μm or less and containing at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F). (Technical proposal 16) A magnetic wedge described in any one of Technical Solutions 1 to 15, having a difference in coercive force depending on the direction within the flat surface of the flat magnetic metal particle. (Technical proposal 17) A magnetic wedge according to any one of technical proposals 1 to 16, having a difference in coercive force depending on the direction within a plane parallel to the flat surface. (Technical proposal 18) A rotating electric machine equipped with the magnetic wedge described in any one of technical proposals 1 to 17. [Explanation of symbols]
[0139] 6: flat surface 9: Covering layer 10: Flat magnetic metal particles 20: Intervening phase 100:Magnetic wedge 200: Rotating motor 210: Rotor 220: Stator 222: Stator core 230: Coil 232: Excitation coil 234:Armature coil 240 :Void surface 250: Iron core teeth 260: Core slot 270: Stator 280: Axis 290: Mover
Claims
1. A magnetic wedge for a rotating electric machine, the magnetic wedge comprising a plurality of flat magnetic metal particles and an intervening phase; A magnetic wedge having a surface coating layer on at least a portion of a surface of the magnetic wedge.
2. 2. The magnetic wedge of claim 1, wherein the thickness of said surface coating layer is equal to or greater than the average thickness of said flat magnetic metal surface particles.
3. 2. The magnetic wedge of claim 1, wherein said surface coating layer comprises a resin.
4. 2. The magnetic wedge according to claim 1, wherein the surface coating layer is made of a resin whose weight increase rate after exposure to the atmosphere at 120[deg.] C. for 30 minutes and then to the atmosphere at room temperature for one week is 1% or less.
5. 2. The magnetic wedge according to claim 1, wherein the surface coating layer has a water absorption rate of 1% or less as defined by ISO 62:1999 (JIS K7209:2000).
6. 2. The magnetic wedge according to claim 1, wherein the surface coating layer contains at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenol resins, epoxy resins, and silicone resins.
7. In a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, The magnetic wedge of claim 1 , wherein among the plurality of flat magnetic metal particles, there are flat magnetic metal surface particles, of which 10% or more of the length of the flat magnetic metal particles is arranged outside the average contour line in the width direction of the magnetic wedge.
8. A magnetic wedge as described in claim 1, wherein in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, flat magnetic metal surface particles having 10% or more of their length positioned outside the average contour line of the width direction of the magnetic wedge account for 1% or more and 90% or less of the total number of flat magnetic metal surface particles.
9. A magnetic wedge as described in claim 1, wherein in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, the orientation angle of flat magnetic metal surface particles, which are arranged outside the widthwise contour average line of the magnetic wedge for more than 10% of their length, is 1 degree or more and 60 degrees or less with respect to the widthwise contour average line.
10. 2. The magnetic wedge according to claim 1, wherein a surface roughness Ra of a widthwise contour line in a cross section perpendicular to the longitudinal direction of the magnetic wedge and taken at the center of the longitudinal direction is 0.1 μm or more and 100 μm or less.
11. The magnetic wedge according to claim 1, wherein the intervening phase is present between the flat magnetic metal particles and contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F).
12. The magnetic wedge of claim 1 , wherein the intervening phase comprises a resin.
13. 2. The magnetic wedge according to claim 1, wherein the intervening phase contains at least one resin selected from the group consisting of bismaleimide-based resins, polyimide-based resins, polyester-based resins, phenol-based resins, epoxy-based resins, and silicone-based resins.
14. A magnetic wedge as described in claim 1, wherein the plurality of flat magnetic metal particles have an average thickness of 10 nm or more and 100 μm or less, have a magnetic metal phase containing at least one first element selected from the group consisting of Fe, Co and Ni, and have an average ratio of the average length within the flat surface to the thickness of 5 or more and 10,000 or less.
15. A magnetic wedge as described in claim 1, wherein at least a portion of the surface of the flat magnetic metal particle is covered with a coating layer having a thickness of 0.1 nm or more and 1 μm or less and containing at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F).
16. 2. The magnetic wedge according to claim 1, wherein the flat magnetic metal particles have a difference in coercivity depending on the direction within the flat plane.
17. 2. The magnetic wedge according to claim 1, wherein the magnetic wedge has a difference in coercivity depending on a direction in a plane parallel to the flat surface.
18. A rotating electric machine comprising the magnetic wedge according to claim 1.
Citation Information
Patent Citations
Improvements relating to magnetic structures
GB923296A
Plural flat magnetic metal particles, pressed powder material, and rotary electric machine
JP2018152449A
Magnetic wedge and rotary electric machine
JP2019058014A
Magnetic wedge manufacturing method, magnetic wedge, stator for rotating electrical machine, and rotating electrical machine
JP2022126604A
Magnetic wedge and rotating electrical machine
US20190238021A1